Improving Students’ Math Writing Skills and Interest Through Online-Based Flipped Classroom Models - Jaka Wijaya Kusuma; Isnaini Mahuda; Hamidah; Pardomuan Robinson Sihombing; Saeful Hidayat (Bandung Conference Series: Mathematics, 2022)
Abstract. In today's advanced technological era, the online-based flipped classroom learning model can overcome online learning problems while improving students' mathematical writing skills and interest in learning. The study aims to improve students' mathematical writing skills and interest in learning with an online-based flipped classroom learning model. The type of research is classroom action research (PTK) with a postest only one group design. The research subjects were 38 students majoring in mathematics education at Bina Bangsa University for the 2019-2020 academic year in the even semester. There are four stages of PTK which are carried out in several cycles, namely the planning stage, implementing actions, observation, and reflection. From the results of this study, it was concluded that the online-based flipped classroom model is effective in improving students' mathematical writing skills. Furthermore, it is concluded that students' learning experiences after being given learning with an online-based flipped classroom model, the majority of which are classified as high. Abstrak. Di era teknologi yang semakin maju saat ini, model pembelajaran flipped classrom berbasis online dapat mengatasi permasalahan pembelajaran online sekaligus meningkatkan kemampuan menulis matematis dan minat belajar siswa. Penelitian ini bertujuan untuk meningkatkan keterampilan menulis matematis dan minat belajar siswa dengan model pembelajaran flipped classroom berbasis online. Jenis penelitian ini adalah penelitian tindakan kelas (PTK) dengan desain postest only one group design. Subyek penelitian adalah 38 mahasiswa jurusan pendidikan matematika Universitas Bina Bangsa tahun ajaran 2019-2020 semester genap. Ada empat tahapan PTK yang dilakukan dalam beberapa siklus, yaitu tahap perencanaan, pelaksanaan tindakan, observasi, dan refleksi. Dari hasil penelitian ini disimpulkan bahwa model flipped classroom berbasis online efektif dalam meningkatkan kemampuan menulis matematis siswa. Selanjutnya disimpulkan bahwa pengalaman belajar siswa setelah diberikan pembelajaran dengan model flipped classroom berbasis online mayoritas tergolong tinggi.